# If $P = (1+ \cos x)(1+ \cos y)(1+ \cos z) = (1- \cos x)(1- \cos y)(1- \cos z)$, then $P = |\sin x\sin y \sin z|$ [closed]

If we know ... $$P = (1+ \cos x)(1+ \cos y)(1+ \cos z) = (1- \cos x)(1- \cos y)(1- \cos z)$$ ... then prove ... $$P = |\sin x\sin y \sin z|$$

## closed as off-topic by user299912, Claude Leibovici, Stefan Mesken, Ferra, s.harpNov 24 '16 at 12:06

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – MathematicsStudent1122, Claude Leibovici, Stefan Mesken, Ferra, s.harp
If this question can be reworded to fit the rules in the help center, please edit the question.

• What is $\P$? what did you try? – Iuli Nov 24 '16 at 7:37

Compute $P^2$ by multiplying the two different expressions. Use difference of squares and a basic trig identity.

Notice,

$$P^2 = P \cdot P = (1+\cos x)(1+\cos y)(1+\cos z) \cdot (1-\cos x)(1-\cos y)(1-\cos z)$$ $$=(1+\cos x)(1-\cos x)\cdot (1+\cos y)(1-\cos y)\cdot(1+\cos z)(1-\cos z)$$ $$=(1-\cos^2x)(1-\cos^2y)(1-\cos^2z)$$

Then, applying the identity $\sin^2x+\cos^2x = 1$ yields,

$$P^2 = \sin^2x \cdot \sin^2y \cdot \sin^2z = (\sin x \cdot \sin y \cdot \sin z)^2.$$

Applying the square root to both sides, $$|P| = |\sin x \cdot \sin y \cdot \sin z|.$$

Since $1+\cos x \geq0$ for all $x$, one can show that $P$ is non-negative and thus $|P| = P$ so we finally have, $$P = |\sin x \cdot \sin y \cdot \sin z|.$$